The Role of Media on the Intention of Adolescents Smoking: A Systematic Review and Meta-Analysis - Majid Barati; Hanieh Jormand; Saeed Bashirian; Amin Doosti-Irani; Forouzan Rezapur-Shahkolai (Hamadan University of Medical Sciences, 2020)
Aims: Smoking in adolescents show worrying trends, and at this age, media threats and media attention increases. Therefore, to determine the role of media in the intentions to smoke in adolescents, this study was conducted. Information & Methods: The systematically electronic search from international databases including Medline, Web of Science, Scopus, and Science Direct until April 2019 was conducted, and observational studies addressing the associations between media exposure and smoking in adolescents aged 10 to 19 years were analyzed. The results of related studies were evaluated with the Newcastle and Ottawa Guidelines and the JBI (The Joanna Briggs Institute), and Chi2 and I2 statistics assessed between-studies heterogeneity. Findings: In this study, 20 articles were entered, and 13 articles were included in the meta-analysis. The ORs (95% CI) exposure to the media contents associated with intentions to smoke in adolescents was as follows: in persuasive media OR=1.27 (95% CI 0.98, 1.64) and protective media OR=0.76 (95% CI 0.67, 0.86) with the intention of smoking in adolescents. Also, films with cigarette content were considered the strongest media were encouraging the intention to smoke OR=1.54 (95% CI 0.91, 2.59). Conclusion: The present study provided a clear picture of mediachr('39')s role and how a medium platform influences the intention of smoking among adolescents and emphasizes the need to acquire and improve media literacy skills to prevent them.